Screening children for pulmonary arteriovenous malformations: Evaluation of 18 years of experience. Issue 9 (13th April 2017) - Hosman, Anna E.; de Gussem, Els M.; Balemans, Walter A. F.; Gauthier, Andréanne; Westermann, Cees J. J.; Snijder, Repke J.; Post, Marco C.; Mager, Johannes J.
Abstract: Background: Hereditary Hemorrhagic Telangiectasia (HHT) is an autosomal dominant disease with multi‐systemic vascular dysplasia. Early diagnosis through screening is important to prevent serious complications. How best to screen children of affected parents for pulmonary arteriovenous malformations (PAVMs) is often subject to debate. Transthoracic contrast echocardiogram (TTCE) is considered optimal in screening for PAVMs in adults. Guidelines for the screening of children are not specific, reflecting the lack of scientific evidence on the best method to use. Objective: Aims of this study are (i) to evaluate our current screening method, consisting of history, physical examination, pulse oximetry, and chest radiography and (ii) to assess whether postponing more invasive screening for PAVMs until adulthood is safe. Methods: This is a prospective observational cohort study using a patient database. Results: Over a period of 18 years (mean follow‐up 9.21 years, SD 4.72 years), 436 children from HHT families were screened consecutively. A total of 175/436 (40%) children had a diagnosis of HHT. PAVMs were detected in 39/175 (22%) children, 33/39 requiring treatment by embolotherapy. None of the screened children suffered any PAVM‐associated complications with this screening method. Conclusion: This study shows that a conservative screening method during childhood is sufficient to detect large PAVMs and protect children with HHT for PAVM‐related complications. Postponing TTCE and subsequent chest CT scanning until adulthood to detect any smaller PAVMs does not appear to be associated with major risk.